When John Smith Arrived in Space - Caravella, Maya (Journal of Artistic Creation and Literary Research, 2025)
The courageous, reckless, slightly-outlaw, strong, white man has been set as a symbol for the American identity, and as the United States themselves were, it was modelled by a migrant - a young English soldier from the 16th century who could not ignore the call of adventures: John Smith. The main aim of this essay is to explore how the idealization of this character of the Renaissance has been used throughout the History of the United States as a tool to impulse nationalism, creating in society a need to fix itself to certain canons so that they could be crowned as “perfect and valuable Americans” whose duty and destiny was to expand through the territory no matter the cost (usually human lives) to increase the power of the country; starting from the expansion of the US Frontier during the Conquer of the West - John Smith as the cowboy; until the 20th century, when the silent war against the USSR led the US government to impulse the Space Race - John Smith as an astronaut. By firstly analyzing what made John Smith a national hero, this essay will compare him with the myth of the cowboy, together with the ideal and current American hero that is set in the astronaut - portrayed in the popular culture through mass media (cinematography) and studied in this work taking John Waine (the American cowboy) and Matthew McConaughey in Christopher Nolan’s Interstellar as concrete examples of this matter.